Resident Perception of Conflict with Tourism Enterprise: An Investigation at A Mountainous Destination in Vietnam - Hien, Duong Thi; Thanh, Tran Duc (E-Journal of Tourism; Volume 9 Number 2 (September 2022), 2022)
Based on extended social exchange theory, the authors propose a framework to investigate the conflict of local residents with tourism businesses. The authors applied a random sampling method and approached 388 residents living in Pu Luong Nature Reserve, a renowned community based tourism destination in Thanh Hoa mountainous area, Vietnam. The findings show that resident’s conflict with tourism business is influenced by latent variables: community’s involvement, perceived benefit and perceived cost. This study is an additional contribution to the theoretical perspective of tourism conflict. In addition, some practical implications are made for local authorities to promote sustainable tourism. Keywords: Conflict, mountainous destination, resident, stakeholder relationship, tourism enterprise